IDENTIFIKASI SPUTUM CULTURE BERDASARKAN KARAKTERISTIK PADA PENDERITA TB PARU YANG MENGKONSUMSI OBAT ANTI TUBERKULOSIS (OAT) - Kurnia Sandi; Siti Rahmalia Hairani Damanik; Yesi Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Mycobacterium tuberculosis can be detected on sputum by microscopic and culture. By the sputum culture, BTA can be checked from the sample of secret. Patient compliance in taking medication regularly is one of the factors that determine the success full in the medication of pulmonary tuberculosis. This research aimed to determine the characteristics of sputum culture of patients with pulmonary tuberculosis that taking anti tuberculosis drugs. The design of this research was descriptive analitic with cross sectional approach. Study was conducted in Puskesmas Harapan Raya Pekanbaru with 40 samples were selected using purposive sampling technique. This research used observation sheet about BTA examination that on registration sheet in community health center. The analysis use were univariat analysis to find the frequency distribution and descriptions of acid resistant bacil. The result showed that there was differences sputum culture based on characteristics of patient with pulmonary TB. Based on the result of this study, expected to health workers to explain how to evaluate the secretion optimally to patient with pulmonary tuberculosis, and also health workers should suggest the patient for taking medication regularly to be better condition. Keywords: Adherence, anti tuberculosis drugs, sputum culture